2019
DOI: 10.1080/10715762.2019.1575512
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol suppresses nitric oxide synthases and the angiogenesis pathway in colorectal cancer

Abstract: The thunder god vine (Tripterygium wilfordii Hook. F) is traditionally used for inflammationrelated diseases in traditional Chinese medicine. In recent years, celastrol (a natural compound from the root of the thunder god vine) has attracted great interest for its potential anticancer activities. The free radical nitric oxide (NO) is known to play a critical role in colorectal cancer growth by promoting tumour angiogenesis. However, how celastrol influences the NO pathway and its mechanism against colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Our recent study [ 66 ] demonstrated that celastrol (tripterine), extracted from the thunder god vine, inhibited the activities of iNOS and eNOS in CRC cells. The inhibitory effects in cell growth and migration were associated with the angiogenesis pathway.…”
Section: Nos Inhibitors: Targeting Nos In Colon Cancermentioning
confidence: 99%
“…Our recent study [ 66 ] demonstrated that celastrol (tripterine), extracted from the thunder god vine, inhibited the activities of iNOS and eNOS in CRC cells. The inhibitory effects in cell growth and migration were associated with the angiogenesis pathway.…”
Section: Nos Inhibitors: Targeting Nos In Colon Cancermentioning
confidence: 99%
“…Suppression of the expression of key genes (TYMP, CDH5, THBS2, LEP, MMP9, and TNF) and proteins (IL-1b, MMP-9, PDGF, Serpin E1, and TIMP-4) involved in the angiogenesis pathway [495]. Reduces the cell size of the SP (side population) increases frequency of apoptosis and binds to Pgp protein in cell membranes inhibiting its transport function [496]. Inhibits CRC cell proliferation and migration through suppression of MMP3 and MMP7 by the PI3K/AKT signaling pathway [497].…”
Section: Rootmentioning
confidence: 99%
“…It is a potent antioxidant evidenced by inhibiting lipid peroxidation (Bian et al 2016) and an antiinflammatory agent by balancing pathogenic and regulatory T cells (Astry et al 2015). What's more, it exhibits an anti-cancer capacity evidenced by anti-angiogenic properties (Gao et al 2019). However, there are few reports that tripterine has shown clinical activity in scarring formation.…”
Section: Introductionmentioning
confidence: 99%